Relationship between small ruminants behaviour and landscape features in Northeast of Portugal - Castro, Marina (2012)
The small ruminant production systems in Northeastern Portugal are mainly based on the extensive exploitation of the spontaneous plant production. The shepherds direct their flocks on daily grazing itineraries across different patches of land use. Sheep and goats flocks were monitored monthly for a year. Data collected consists of geographical position and the type of land use crossed. Also, essential livestock activities were monitored. The corrected frequencies (preference indexes) approach was used for the data analysis. The principal aims were to examine the relationships between livestock behaviour and land use types, and to check how they change throughout the year and the time of day. Our results showed a strong dependence between land use types and livestock activities and suggested a considerable coherence between human management, the spontaneous behaviour and physiological needs of animals and the agroecosystems capacity to supply the livestock needs.